(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This scientific article presents the author’s approach to the assessment and selection of the bottom of the drill string assembly (BHA) in the construction of vertical and directional wells. Functional features of BHA, their influence on the formation of the wellbore trajectory, well stability and drilling efficiency are considered. Special attention is paid to the comprehensive analysis of geological and technical factors that determine the choice of the arrangement, as well as the substantiation of rational solutions, aimed at reducing complications and improving the economic performance of drilling.